Acupuncture for Pain Management: Molecular Mechanisms of Action - Chen, Teng; Zhang, Wen Wen; Chu, Yu-Xia; Wang, Yan-Qing (The American journal of Chinese medicine (1979), 2020)
Acupuncture reduces pain by activating specific areas called acupoints on the patient's body. When these acupoints are fully activated, sensations of soreness, numbness, fullness, or heaviness called De qi or Te qi are felt by clinicians and patients. There are two kinds of acupuncture, manual acupuncture and electroacupuncture (EA). Compared with non-acupoints, acupoints are easily activated on the basis of their special composition of blood vessels, mast cells, and nerve fibers that mediate the acupuncture signals. In the spinal cord, EA can inhibit glial cell activation by down-regulating the chemokine CX3CL1 and increasing the anti-inflammatory cytokine interleukin-10. This inhibits P38 mitogen-activated protein kinase and extracellular signal-regulated kinase pathways, which are associated with microglial activation of the C-Jun N-terminal kinase signaling pathway and subsequent astrocyte activation. The inactivation of spinal microglia and astrocytes mediates the immediate and long-term analgesic effects of EA, respectively. A variety of pain-related substances released by glial cells such as the proinflammatory cytokines tumor necrosis factor , interleukin-1 , interleukin-6, and prostaglandins such as prostaglandins E2 can also be reduced. The descending pain modulation system in the brain, including the anterior cingulated cortex, the periaqueductal gray, and the rostral ventromedial medulla, plays an important role in EA analgesia. Multiple transmitters and modulators, including endogenous opioids, cholecystokinin octapeptide, 5-hydroxytryptamine, glutamate, noradrenalin, dopamine, -aminobutyric acid, acetylcholine, and orexin A, are involved in acupuncture analgesia. Finally, the "Acupuncture " strategy is introduced to help clinicians achieve better analgesic effects, and a newly reported acupuncture method called acupoint catgut embedding, which injects sutures made of absorbable materials at acupoints to achieve long-term effects, is discussed.